Intra- and inter-field diversity of 2, 4-dichlorophenoxyacetic acid-degradative plasmids and their tfd catabolic genes in rice fields of the Mekong delta in Vietnam. Issue 1 (30th October 2018) - Nguyen, Thi Phi Oanh; Hansen, Martin Asser; Hansen, Lars Hestbjerg; Horemans, Benjamin; Sørensen, Søren Johannes; De Mot, René; Springael, Dirk
Abstract: The tfd genes mediating degradation of the herbicide 2, 4-dichlorophenoxyacetic acid (2, 4-D) differ in composition and organization in bacterial isolates from different geographical origin and are carried by different types of mobile genetic elements (MGE). It is not known whether such global diversity of 2, 4-D-catabolic MGE and their tfd gene cargo is reflected in the diversity at field scale. The genomic context of the 2, 4-D catabolic genes of 2, 4-D-degrading isolates from two rice fields with a 2, 4-D application history, located in two distant provinces of the Vietnam Mekong delta, was compared. All isolates were β -proteobacteria, were unique for each rice field and carried the catabolic genes on MGE and especially plasmids. Most plasmids were IncP-1 β plasmids and carried tfd clusters highly similar to those of the IncP-1 β plasmid pJP4, typified by two chlorophenol catabolic gene modules ( tfd-I and tfd-II ). IncP-1 β plasmids from the same field showed small deletions and/or insertions in accessory metabolic genes. One plasmid belonged to an unclassified plasmid group and carries a copy of both tfdA and tfd-II identical to those in the IncP-1 β plasmids. Our results indicate intra-field evolution and inter-field exchange of 2, 4-D-catabolic IncP-1 β plasmids as well as the exchange of tfd genes between different plasmids within a confined local environment. Abstract : Structural analysis of 2, 4-D catabolic plasmids isolated from two different fields in Vietnam suggests intra-field evolution and inter-field plasmid exchange as well as the exchange of tfd genes between different plasmids within a confined local environment.